Chemical synthesis and charge transport mechanism in solution processed flexible polypyrrole films. (November 2015) - Taunk, Manish; Chand, Subhash
Abstract: Polypyrrole (PPy) has been synthesized by a chemical oxidation method using ammonium persulfate to obtain a solution processable PPy powder. The resultant PPy powder was then solution processed to deposit flexible thin films of PPy over flexible substrates. PPy film samples were then characterized using UV–vis spectroscopy, FTIR spectroscopy and X-ray diffraction. It was found that conductivity of PPy ( σ =2.4×10 −2 S/cm) reduces by an order of magnitude after solution processing in the form of films. The temperature dependent conductivity of PPy pellet and flexible films of PPy were measured in the temperature range of 80–300 K. It was observed that PPy films show stronger temperature dependence than pelletized samples. Charge transport in PPy samples has been investigated using Kivelson׳s and Mott׳s variable range hopping models. Mott׳s parameters such as density of states at the Fermi level N ( E F ), average hopping distance ( R ) and average hopping energy ( W ) have been estimated for PPy samples. The results showed that at room temperature average hopping distance for PPy film was about 22.3 Å and average hopping energy was 128.6 meV.